Success factors in social entrepreneurial start-ups among mature women in Aotearoa New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Business Sustainability at Massey University, Manawatū, Aotearoa New Zealand - Cardiff, Kathlyn (Massey University, 2026)
Although women are living longer, their employability or ability to find work diminishes with age, effectively creating a shortened runway for their financial stability in their later years. Entrepreneurship is proposed as a viable solution for extending the working lives of mature women (over 50). Mature women tend to move into social entrepreneurial startups when they set up ventures. However, little is known about what contributes to successful outcomes when starting a social enterprise in Aotearoa New Zealand. An initial focused review of literature on mature women’s social entrepreneurship revealed a lack of research regarding their experiences. Consequently, a wider literature was collated and analysed to identify themes common across relevant studies to identify theories, concepts and models on which to build a conceptual framework of what is known and not known about mature women social entrepreneurs. Data collection and analysis were performed in accordance with Interpretative Phenomenological Analysis (IPA) (Smith & Nizza, 2022). Informed by phenomenology, first person in-depth accounts from five mature women social enterprise founders were conducted. Cases were analysed idiographically (case-by-case). In all, seven Group Experiential Themes (GETs) were identified: starting out, funding challenges, entrepreneurship as continuous learning, building and managing relationships, founder identity, support wanted, and reflections. Results were discussed in relation to the existing literature. While findings suggest mature women entrepreneurs, and indeed social entrepreneurs, share challenges similar to their younger counterparts, a sense of purpose and resilience appears to set them apart. Themes shared between participants in this study and those in the literature review material are: challenges with securing funding; limited access to business skills development; limited access to mentoring opportunities; and few opportunities for building networks. Considerations include this study’s small sample size, although the use of IPA mitigates this as it is a method suited to systematic in-depth analysis of the type conducted in this research project. Success of these women and future social entrepreneurial women could be enhanced through providing tailored support during start-up which is necessary to overcome the challenges identified.
Keywords: 350704 Entrepreneurship; 350716 Small business organisation and management